(untitled) (El Hilo de la Fabula, 2010)
In this work, the platonic doctrine of the elements in the Thimaeus is analized in relation with the critic that Aristotle makes to it in the De Caelo III 7-8. The mathematical aspects of the critic are particularly studied showing the connection with the Aristotelian conception of the elements itself. On the other hand, the position of the observation in the Platonic and Aristotelian explanations of the elements is comparatively valued.